Canada : what it is, what it can be - Martin, Roger L.; Milway, James, 1951- (Toronto [Ont.] : University of Toronto Press, 2012)
Written in an accessible style that helps general readers understand complex economic concepts, Canada: What It Is, What It Can Be exposes the myths currently guiding our public policy, and provides ground-breaking new approaches for realizing our full prosperity potential.
Part One Working More But Not Smarter -- Chapter 1: What Are Competitiveness and Prosperity? -- Chapter 2: How Much Are We Working for Prosperity? -- Chapter 3: How Much Value Are We Creating When We Are Working? -- Part Two What Drives Our Productivity and Innovation Performance? -- Chapter 4: How Does Where We Live and Work Matter? -- Chapter 5: How Do We Compete? -- Chapter 6: How Do We Invest? -- Part Three Recommendations for Achieving Our Prosperity Potential -- Chapter 7: Tax Smarter for Prosperity -- Chapter 8: Make Public Policy on Innovation More Innovative -- Chapter 9: Strengthen Management Talent -- Chapter 10: Bulk Up, Not Hollow Out -- Chapter 11: Become a True Trading Nation -- Chapter 12: Focus on Poverty, Not Inequality -- Chapter 13: Make Canada What It Can Be -- Epilogue.
Includes bibliographical references and index.
JSTOR
Keywords: Labor productivity -- Canada; Competition -- Canada; Economic development -- Canada; Economic forecasting -- Canada; Canada -- Economic policy; Productivité -- Canada; Développement économique -- Canada; Prévision économique -- Canada; BUSINESS & ECONOMICS -- General; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Competition; Economic development; Economic forecasting; Economic policy; Labor productivity; Canada; Volkswirtschaft; Wirtschaftswachstum; Wettbewerb; Innovation; Produktivität.; Wirtschaftspolitik; Kanada